Designing A Company Performance Appraisal System With the Balance Score Card Method - Winarno, Heru; Syamsudin; Syaina Azzahra; Angga Baghaskara (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
AbstractIntense competition does not look at the size of a company, in order to be productive and innovate, requires the role and task of resources in the business field that lie in the ability to act according to the company's targets. Human resources have a very crucial role in a company. Without human resources, the company will not be able to run well in achieving its goals. Human Resource Management in its operation requires performance that must be developed, especially for service industries and services supported by the design of a measurable employee performance assessment system by applying the Balanced Score Card method. Companies certainly want steps and strategies in implementing the design of a performance appraisal system in an effort to maximize the company's role in order to run and compete competitively. The purpose of this research is to determine the design of a service company performance appraisal system using the Balanced Scorecard approach. The population and sample in this study are the Tribuana 1 Cooperative Primary Company. The method in this study is a qualitative descriptive approach using interviews and observations. The result of this research is the design of a Performance Appraisal system based on four perspectives contained in the Balanced Scorecard, the first is the financial perspective, which is used as a basis for the consequences of economic actions. The second perspective, the customer perspective, is a market segment where companies must adjust the level of satisfaction, loyalty, retention, and customer acquisition. The third perspective is the perspective of internal business processes, carrying out the process of measuring and innovating products to have added value, the fourth perspective is the perspective of growth and development, improving the quality of results, productivity and improving resource welfare.Keywords: Balanced Scorecard; Human Resource Management; Performance Appraisal